Distinct characteristics of unique immunoregulatory canine non-conventional TCRαβpos CD4negCD8αneg double-negative T cell subpopulations - Karwig, Laura; Moore, Peter F.; Alber, Gottfried; Eschke, Maria (Frontiers in Immunology, 2024)
Conventional CD4pos regulatory T (Treg) cells characterized by expression of the key transcription factor forkhead box P3 (FoxP3) are crucial to control immune responses, thereby maintaining home-ostasis and self-tolerance. Within the substantial population of non-conventional T cell receptor (TCR)αβpos CD4negCD8αneg double-negative (dn) T cells of dogs, a novel FoxP3pos Treg-like subset was described that, similar to conventional CD4pos Treg cells, is characterized by high expression of CD25. Noteworthy, human and murine TCRαβpos regulatory dn T cells lack FoxP3. Immunosuppres-sive capacity of canine dn T cells was hypothesized based on expression of inhibitory molecules (interleukin (IL)-10, cytotoxic T-lymphocyte associated protein 4, CTLA4). Here, to verify their reg-ulatory function, the dnCD25pos (enriched for FoxP3pos Treg-like cells) and the dnCD25neg fraction, were isolated by fluorescence-activated cell sorting from peripheral blood mononuclear cells (PBMC) of Beagle dogs and analysed in an in vitro suppression assay in comparison to conventional CD4posCD25pos Treg cells (positive control) and CD4posCD25neg T cells (negative control). Canine dnCD25pos T cells suppressed the Concanavalin A-driven proliferation of responder PBMC to a sim-ilar extent as conventional CD4posCD25pos Treg cells. Albeit to a lesser extent than FoxP3-enriched dn and CD4posCD25pos populations, even dnCD25neg T cells reduced the proliferation of responder cells. This is remarkable, as dnCD25neg T cells have a FoxP3neg phenotype comparable to non-suppressive CD4posCD25neg T cells. Both, CD25pos and CD25neg dn T cells, can mediate suppression independent of cell-cell contact and do not require additional signals from CD4posCD25neg T cells to secrete inhibitory factors in contrast to CD4posCD25pos T cells. Neutralization of IL-10 completely abrogated the suppression by dnCD25pos and CD4posCD25pos Treg cells in a TranswellTM system, while it only partially reduced suppression by dnCD25neg T cells. Taken together, unique canine non-conventional dnCD25pos FoxP3pos Treg-like cells are potent suppressor cells in vitro. Moreover, inhibition of proliferation of responder T cells by the dnCD25neg fraction indicates suppressive func-tion of a subset of dn T cells even in the absence of FoxP3. The identification of unique immuno-regulatory non-conventional dn T cell subpopulations of the dog in vitro is of high relevance, given the immunotherapeutic potential of manipulating regulatory T cell responses in vivo.